Multinational business finance - Eiteman, David K.; Stonehill, Arthur I. (Reading, Mass. : Addison-Wesley Pub. Co., 1979)
This second edition of the book is appropriate for the same audience as the first edition (1973). The reason for this thorough revision is a change in the priorities of financial executives and academics caused by floating exchange rates, combined with changes in the way financial executives and accountants view foreign exchange gains and losses.
Includes bibliographical references and index.
hza 03/08/2018
Loans
Keywords: International business enterprises